Pengaruh Use of Sosmed dan Motivasi Berwirausaha Terhadap Minat Berwirausaha Melalui Variabel Intervening Efikasi Diri - Premaytri Yuwinda Athifa Dhitara; Eka Hendi Ardiansyah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Research motivated by the low interest in entrepreneurship students. Research see the effect use of sosmed and entrepreneurship motivation on entrepreneurship interest through self-efficacy intervening variable. Research type correlational with a quantitative approach. Sampling research as 121 students economic education study program in UNESA. Data analysis method with WarpPLS. The results are (1) use of sosmed and self-efficacy on interest in entrepreneurship partially have a significant and positive effect; (2) entrepreneurial motivation on self-efficacy partially has a significant and positive effect; (3) entrepreneurial motivation on interest in entrepreneurship partially has no significant and positive effect; (4) the use of sosmed on self-efficacy partially has no significant and positive effect; (5) simultaneously the intervening variable self-efficacy does not mediate between use of sosmed and interest in entrepreneurship, but mediates between entrepreneurial motivation variables and interest in entrepreneurship